KAJIAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA PADA MATERI PERSAMAAN GARIS LURUS DI KELAS VIII SMP NEGERI 6 PALANGKA RAYA - Dina Damiyanti Hidayat; Walter Punding; Sugiharto . (JURNAL PENDIDIKAN, 2022)
This research is motivated by the low problem solving ability of students in solving straight line equations. The purpose of this study was to describe the mathematical problem solving ability of students on the material of straight line equations in class VIII-9 SMP Negeri 6 Palangka Raya. The subjects of this study were students of class VIII-9 of SMP Negeri 6 Palangka Raya out of 33 students only 26 students took the test. Then from 26 students 3 students were taken with high, medium, and high abilities, low to be interviewed. Based on the results of data analysis of students mathematicaproblemsolving abilities in solving straight line equations from 26 students, it was obtained that 2 students had problem solving abilities that were included in the "high" category, 3 students were included in the "medium" category, and 21 students fall into the "low" category. The results obtained in this study are: 1) students' mathematical problem solving abilities are high category, the problem can be understood and the settlement plan can be prepared properly, can carry out the settlement plan properly, and review the answers; 2) students mathematical problem solving abilities are in the medium category, the problem can be understood well, the settlement plan can be prepared well but it is not appropriate to carry out the completion plan and can review the answers; 3) students mathematical problem solving ability is low category, the problem can be understood, has not been able to make a settlement plan, and cannot carry out the settlement plan, and does not look back at the answer.